Nurse’s knowledge, attitude, and practices in the management of childhood fever in Nablus Hospitals - Bilal Mwas; Omar Abureesh (My University, 2016)
Fever is the most common reason for parents to seek medical health care. Most fevers are not serious, they are a local reaction to protect the host and preserve normal body functions; however, many nurses report concern that their child’s fever may cause convulsions or brain damage. This issue may be more serious in the Palestinian healthcare context, where both traditional and western health practices are common and limited research findings are reported. Other common practices believed to reduce body temperature include sponging, bathing or coin massage. International reports show that the fever management practices of parents are learnt from health care professionals. It is important to understand where they learn to manage fever and what information is provided to them in the community setting. This research focused on nurses knowledge, beliefs and practice related to childhood fever management; therefore, it was also important to what factors Influenced their fever management practices. In order to address the problem of ineffective fever management practices and the misuse of medication to reduce Childhood fever. Methodology: Quantitative Cross-sectional survey conducted , Questionnaire tool: pilot study were conducted to ensure the items were clear. Recruitment procedures for the convenience sample for the pilot study (10 nurses) and cross-sectional surveys, Minor modifications were undertaken prior to conducting the surveys Participants (100 nurses) who works in 4 governmental and private hospitals in Nablus District. Result: the most age group more than 30 years old, the gender of participant report that 59 female and 41 male, the year of work experience for them vary from 1 to more than 16 years In some area of fever management Inconsistent knowledge about fever, non-evidence-based beliefs and practices among nurses were identified. Nurses reported negative beliefs about fever, using antipyretics and/or tepid sponging effects. Despite believing fever was a beneficial sign of illness and a response to fight infection, many nurses perceived the use of antipyretics as necessary to prevent febrile convulsions. Many nurse advice parents to used antipyretics and tepid sponging to reduce a mild fever at a mean temperature of 38ºC. Nurses don’t reported social approval for antipyretic administration and they don’t accept receiving conflicting information about this practice. Findings from this research program have provided evidence that nurses have good knowledge in area of detention of fever, antibiotic use and antipyretic and they have limited knowledge or non-evidence-based management for febrile children in part of the most common concern of fever is febrile convulsion and brain damage and parent’s education. More importantly, parent’s education so one of the first recommendation to focus on parent’s education in area of all aspect related to fever. In conclusion, this study data suggests that implementation of educational programs and using guidelines regarding the proper management of the febrile child are needed. There were misconceptions about management and complications of fever. Conflicting results about fever in the literature also confirm these misconceptions. Nurses need consistent fever management information. There is a need for interventions to inform healthcare policy, practices and research development in relation to integration of the latest scientific evidence-based fever management.